2022
DOI: 10.1007/s13204-022-02461-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nanomaterials on pyocyanin production by Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is a bacterium producing industrially utile metabolites, such as rhamnolipids, biopolymers, and pigments. Pyocyanin, the most studied example of pigments, is a virulence factor that also shows the potential for application in, e.g., agriculture, anticancer therapy, and energy production. Therefore, potential inhibitors and stimulants of pyocyanin production by P. aeruginosa should be studied, and nanomaterials may cause both effects. The study aimed to examine the influence of zinc oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(62 reference statements)
1
6
0
1
Order By: Relevance
“…The above is because pyocyanin is a redox pigment considered an important source of reactive oxygen species (ROS), and their overproduction can generate significant alterations in the bacterial structure. It has been reported that low-dose nanomaterials such as zinc oxide and multi-walled carbon nanotubes stimulate the production of bacterial pigments (Jabłońska et al, 2022). According to our results, the low-dose exposition of CuNPs generates stress in the growth of P. aeruginosa, suggesting the overproduction of pigments from the ECM as a possible protective mechanism for the bacteria in front of the NPs exposition.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The above is because pyocyanin is a redox pigment considered an important source of reactive oxygen species (ROS), and their overproduction can generate significant alterations in the bacterial structure. It has been reported that low-dose nanomaterials such as zinc oxide and multi-walled carbon nanotubes stimulate the production of bacterial pigments (Jabłońska et al, 2022). According to our results, the low-dose exposition of CuNPs generates stress in the growth of P. aeruginosa, suggesting the overproduction of pigments from the ECM as a possible protective mechanism for the bacteria in front of the NPs exposition.…”
Section: Discussionsupporting
confidence: 73%
“…Despite the low doses of CuNPs not demonstrating changes in bacterial growth, the physiological manifestation of pyocyanin (Fig. 5) indicates the possible oxidative stress induction in P. aeruginosa (Hall et al, 2016;Jabłońska et al, 2022). The above is because pyocyanin is a redox pigment considered an important source of reactive oxygen species (ROS), and their overproduction can generate significant alterations in the bacterial structure.…”
Section: Discussionmentioning
confidence: 99%
“…In other setups, pyocyanin production was very low or negligible. Comparing the highest concentration obtained in this research to the results from the smaller scale experiments [60][61][62][63], the product concentration is relatively low, showing that the scaleup of pyocyanin production may be complicated and require a different setup than presented in this research. Research is still scarce on pyocyanin production on a scale larger than conical flask cultivation.…”
Section: Resultsmentioning
confidence: 66%
“…The obtained results showed that the highest aeration rate and impeller speed led to the most efficient pyocyanin production, which is in line with the improved oxygen mass transfer. Moreover, it was previously shown that the low liquid volume ratio to the liquid free surface area could lead to higher pyocyanin production by P. aeruginosa ATCC ® 27853™ [ 60 , 61 ]. Nevertheless, the literature analysis proved that different P. aeruginosa strains may require different culturing conditions for pyocyanin production, e.g., temperature and agitation [ 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interesującym aspektem badań nad oddziaływaniami drobnoustrojów z nanomateriałami jest znaczenie tych interakcji w specyficznej odpowiedzi fizjologicznej komórek. Wśród efektów opisanych dotychczas należy wyróżnić możliwość destabilizacji membran komórkowych, wspomniane aglomerowanie komórek oraz ich pozostałości do nanomateriałów i agregatów złożonych z tych nanostruktur, a także stymulowanie biofilmowania i pobudzanie wytwarzania metabolitów wtórnych, w tym barwników [42,44,67]. Niedawno przeprowadzone badania dowodzą, że charakterystyczne oddziaływanie nanomateriałów z drobnoustrojami może być także wykorzystywane w bioinżynierii procesu produkcji wina.…”
Section: Nanotechnologia W Enologiiunclassified